Antibacterial effect of morphous (poly-crystalline) and amorphous (glass) nano-bioactive glass 45S5 on Streptococcus mutans - Shahoon, Hossein; Niyakan, Mohammad; Behnami, Mona; Behnami, Masoumeh; Shahbazi, Sara; Toori, Roghayeh (Journal of Dental School, 2019)
Objective: Bioactive glass 45S5 is a surface reactive glass-ceramic biomaterial, developed in 1969. BAG 45S5 with particle size of 20-60 nm has the ability of bone regeneration, broad spectrum antibacterial effect, repairs and replaces diseased or damaged bone. The aim of this study was to evaluate the antibacterial activity and determine MIC and MBC values of nano-BAG45S5 on Streptococcus mutans. Methods: In this study the in vitro Antibacterial activity of polycrystalline and glass forms of nano- BAG 45S5 was evaluated. Bacterial susceptibility to test materials was examined by antibiogram test. Afterwards MIC and MBC assays were conducted via broth dilution, disc diffusion and colony count methods. Results: Despite amorphous nano-BAG 45S5, poly-crystalline form had antibiogram negative test result. In broth dilution test, the optical absorbance of test dilution of 50mcg/ml and higher concentrations were equal to negative control’s optical absorbance and their inhibitory zone diameter were measured 10.0mm in disc diffusion test. No colony was observed on the culture media of test dilution of 200mcg/ml and higher concentrations. Conclusion: Streptococcus mutans (ATCC 35668) is not susceptible to poly-crystalline nano- BAG45S5. Amorphous nano-BAG45S5 is bacteriostatic against Streptococcus mutans. MIC and MBC values for amorphous nano-BAG45S5 were 50 ppm and 200 ppm, respectively.